Gender Diversity and Firm Performance: Evidence from Co-operative of Chitwan (Nepalese Journal of Management Research, 2025)
This paper examined the relationship between gender diversity and firm performance by taking the evidences from Co-operatives of Chitwan, Nepal. The study adopted descriptive and casual comaparative research design. Secondary data from annual report of the sampled co-operative were used for the analysis. SPSS and Gretl software were used for data analysis. The data of 90 co-operatives were collected from the annual report of the co-operative and Nepal Federation of Savings and Credit Cooperative Unions (NEFSCUN) and saving and Credit Cooperative Society (SACCOS). Based on the resource dependency theory, by measuring gender diversity as inclusion of female director in the boardroom, this study found the positive and significant relationship between gender diversity and firm performance and firm perfermonance is measured by the Return of Asset (ROA). Further analysis revealed that financial performance is positively related to age, level of education and multiple directorships of the female directors in the boardroom.